An African Quest to Appropriate Jesus (Hekima Review, 2008)
How can Jesus, a first-century Palestinian Jew, be Lord and Saviour in and of Africa in the twenty-first century? This article grapples with this question, exploring the contours of the Jesus of history, traditional Christologies, and African Christologies. The author singles out Jesus’ compassion for the poor and the marginalised as the key to unlocking the door through which Jesus makes an entry into the African context.